2013
DOI: 10.6061/clinics/2013(02)oa15
|View full text |Cite
|
Sign up to set email alerts
|

Interobserver agreement for the spine instability neoplastic score varies according to the experience of the evaluator

Abstract: OBJECTIVES:To evaluate the interobserver agreement for the Neoplastic Spine Instability Score (SINS) among spine surgeons with or without experience in vertebral metastasis treatment and physicians in other specialties.METHODS:Case descriptions were produced based on the medical records of 40 patients with vertebral metastases. The descriptions were then published online. Physicians were invited to evaluate the descriptions by answering questions according to the Neoplastic Spine Instability Score (SINS). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 18 publications
(27 reference statements)
2
19
0
2
Order By: Relevance
“…18 There was almost perfect inter-and intraobserver reliability in the total SINS scores for the three clinically relevant evaluations of tumor-related instability, which can be described as stable (score from 0 to 6), indeterminate (imminent from 7 to 12), and unstable (13 to 18). 8,17,19 We observed that all the examiners rated it as important in daily practice and capable of changing their conduct in relation to a case. One criticism of the SINS score was that the neurological status of the patient, a potential modifier of the treatment approach, is not included in the evaluation.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…18 There was almost perfect inter-and intraobserver reliability in the total SINS scores for the three clinically relevant evaluations of tumor-related instability, which can be described as stable (score from 0 to 6), indeterminate (imminent from 7 to 12), and unstable (13 to 18). 8,17,19 We observed that all the examiners rated it as important in daily practice and capable of changing their conduct in relation to a case. One criticism of the SINS score was that the neurological status of the patient, a potential modifier of the treatment approach, is not included in the evaluation.…”
Section: Discussionmentioning
confidence: 86%
“…10,17 Early detection and proper intervention are critical to minimizing the sequelae from spine metastases, reestablishing function, and maximizing the quality of life. 18 There was almost perfect inter-and intraobserver reliability in the total SINS scores for the three clinically relevant evaluations of tumor-related instability, which can be described as stable (score from 0 to 6), indeterminate (imminent from 7 to 12), and unstable (13 to 18).…”
Section: Discussionmentioning
confidence: 99%
“…The indication for surgical treatment depends of the clinical status of the patients, prognosis, primary tumor and the characteristics of the spinal compression 20 . In our institution, surgery is not routine treatment for patients with compression syndrome, thus, all patients received radiotherapy, and there was no woman underwent surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Junkcionális gerinc (occiput-C2, C7-T2, T11-L1, L5-S1) [7][8][9]. A SINS számos guideline és klinikai vizsgálati protokoll részévé vált [10,11], továbbá két klinikai döntés támogatási rendszerébe is beillesztették.…”
Section: Lokalizációunclassified